Host diet shapes functionally differentiated gut microbiomes in sympatric speciation of blind mole rats in Upper Galilee, Israel - Kuang, Zhuoran; Li, Fang; Duan, Qijiao; Tian, Cuicui; Nevo, Eviatar; Li, Kexin (Frontiers in Microbiology, 2022)
The gut microbiome is important for host nutrient metabolism and ecological adaptation. However, how the gut microbiome is affected by host phylogeny, ecology and diet during sympatric speciation remains unclear. Here, we compare and contrast the gut microbiome of two sympatric blind mole rat species and correlate them with their corresponding host phylogeny, ecology soil metagenomes, and diet to determine how these factors may influence their gut microbiome. Our results indicate that within the host microbiome there is no significant difference in community composition, but the functions between the two sympatric species populations varies significantly. No significant correlations were found between the gut microbiome differentiation and their corresponding ecological soil metagenomes and host phylogeny. Functional enrichment analysis suggests that the host diets may account for the functional divergence of gut microbiome. Our results will help us understand how the gut microbiome changes with corresponding ecological dietry factors in sympatric speciation of blind subterranean mole rats.